Studi Komparasi Jenis Pelarut Ekstraksi terhadap Kandungan Fitokimia Daun Tanaman Kubis Ungu - Bhuana, Hengky Surya; Sritamin, Made; Wirawan, I Gede Putu (Nandur; Vol 1 No 4 (2021), 2021)
Red cabbage is a plant that is rich in antioxidant, one of its secondary metabolites, antosianin that gave the purple color on red cabbage has multiple health effects for human such as preventing cancer, tumor, and many more. The use of this secondary metabolites in plants nowadays is very popular, not only for its pharmacological effects, but also as an antibacterial, coloring agent, flavoring agent, natural pesticide, etc. Therefore, this study is needed to look for another potentially benefical compound in the plant, such as red cabbage, a plant that is more than just a salad. The aim of this study was to determine the effect of the types of extraction solvents on phytochemical compound of red cabbage plant leaves. The dried off plant macerated with two kinds of solvents, aquades, and ethanol. After about + 3 days, both of the extract got evaporated with rotary evaporator. The yields of evaporating will be tested with GCMS analysis. The result showed that kind of extraction solvents do affect the yield from evaporating, and GC-MS analysis. Aquades showed to have a better capability in both of extraction, or on the analysis with GC-MS.